Active surveillance in differentiated thyroid cancer: a strategy applicable to all treatment categories response - Campopiano, Maria Cristina; Ghirri, Arianna; Prete, Alessandro; Lorusso, Loredana; Puleo, Luciana; Cappagli, Virginia; Agate, Laura; Bottici, Valeria; Brogioni, Sandra; Gambale, Carla; Minaldi, Elisa; Matrone, Antonio; et al. (Frontiers in Endocrinology, 2023)
Currently, the differentiated thyroid cancer (DTC) management is shifted toward a tailored approach based on the estimated risks of recurrence and disease-specific mortality. While the current recommendations on the management of metastatic and progressive DTC are clear and unambiguous, the management of slowly progressive or indeterminate disease varies according to different centers and different physicians. In this context active surveillance (AS) becomes the main tool for clinicians, allowing them to plan a personalized therapeutic strategy, based on the risk of an unfavorable prognosis, and to avoid unnecessary treatment. This review analyzes the main possible scenarios in treated DTC patients that could take advantage from AS,